The Influence of Organizational Culture and Teacher Competence on Teacher Commitment in the Implementation of the Merdeka Curriculum - Hajar, Ibnu; Marwan, Marwan; Siraj, Siraj (SAINTIS Publishing, 2025)
One of the important factors influencing the successful implementation of the Merdeka Curriculum is teacher commitment. Teachers are expected to demonstrate a high level of commitment in understanding the curriculum philosophy, applying student-centered learning, and consistently implementing differentiated instruction and Pancasila Student Profile Strengthening Projects. However, variations in teacher commitment indicate the need to examine factors that may strengthen or weaken this commitment. Two factors considered crucial in this context are organizational culture and teacher competence.This study aimed to analyze the influence of organizational culture and teacher competence on teacher commitment in the implementation of the Merdeka Curriculum. The research employed a quantitative approach with a causal research design. Data were collected from 179 elementary school teachers participating in Sekolah Penggerak in North Aceh Regency using a structured questionnaire. The data were analyzed through descriptive statistics and multiple linear regression analysis. The findings revealed that organizational culture has a positive and significant effect on teacher commitment, whereas teacher competence does not show a significant influence. These results indicate that a supportive organizational culture plays a more decisive role in fostering teacher commitment than individual competence alone in the context of curriculum reform.